In Vitro Assays of Mitochondrial Function/Dysfunction. Issue 6 (10th September 2014) - Than, T A; Win, S; Kaplowitz, N
<x xml:space="preserve">Abstract</x> In drug‐induced hepatotoxicity, type 2 diabetes, and alcoholic and nonalcoholic fatty liver diseases, liver mitochondria have been recognized to be dysfunctional. Mitochondrial function can be assessed in isolated mitochondria and in intact cells by using O2‐dependent quenching of porphyrin‐based phosphors or by using amperometric O2 sensors to measure O2 consumption. Clinical Pharmacology & Therapeutics (2014); 96 6, 665–668. doi:10.1038/clpt.2014.178